Perancangan Broadband RF Power Amplifier 2,3 GHz pada 4G LTE Time Division Duplex - Syifaul Fuada (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
This paper reports a design of Broadband RF Power Amplifier TDD 4G LTE operating at frequency 2,3 GHz – 2,36 GHz, according to the working frequency of the service provider Smartfren’s BTS. This RF Power Amplifier uses class A amplifier with GaN HEMT transistor type CREE CGH40120F. This design is simulated using Advanced Power Design program (ADS) version 2014. The simulation results show that the Power Amplifier is stable (K> 1) at a frequency of 2.3 GHz with the S11 and S22 match, generating 43.44 dBm output power 22,08 Watt with a gain of 10.5 dB, return loss of <-5 dB, and maximum power supply efficiency of 39.8%.